Watch dog system for water management. (15th November 2019) - Jothikumar, R.; SivaShanmugam, G.; Susi, S.
Water is one of the basic needs for the existence of the human, animal and plant lives on the earth. There will be a vast need for water all over the world soon. Due to many factors the water is being polluted in many ways. It is necessary to take utmost care of water for future generations. This paper presents a low cost framework design for monitoring of water quality. An IoT-based system to prevent water from getting spoil through environmental factors has been introduced. The water necessity, its dissemination and quality check by an embedded-based novel drew nearer approach is proposed. Water flow sensor, pH sensor, Ultra sonic sensor and PIC microcontroller were used for implementation to provide an accurate check on the availability and properties of water. This low cost real time water monitoring system can also do segregate availability of water for their external and internal uses.